Determination of Emitted Hydrogen (H2) from Bacterial Cultures in Closed Septum Vials by Gas Chromatography (GC) and Specific Hydrogen Sensor Techniques - Kolb, Bruno (Research Perspectives of Microbiology and Biotechnology Vol. 3, 2024)
The present study primarily focuses on the determination of emitted hydrogen (H2) from bacterial cultures in closed septum vials and both techniques, static-GC as well as the sensor approach. When microorganisms are cultivated in suitable nutrient medium in closed septum vials, their emission of hydrogen (H2) is detected using a particular hydrogen sensor in addition to headspace-gas chromatography. Facultative anaerobes are able to release both CO2 and H2 which are important chemicals for both types of bacteria, whereas obligatory aerobic bacteria can only create CO2 and water through aerobic oxidation. Obligate anaerobic bacteria emit H2 too but need an oxygen-free atmosphere which can be achieved if the air in the septum vial is replaced by nitrogen. The samples under investigation, either solid or liquid samples and from smears by wads from a cotton bud, are cultured in the headspace vials and the hydrogen emission was monitored after the necessary time of incubation and thus microbe contamination was detected. Antibiotics added to the bacterial culture in the vial are found to be effective if any gas emission is suppressed. If not, they are either ineffective or the bacteria are even resistant. Antibiotics, both synthetic and natural, were investigated and some were discovered to be resistant or ineffective. This technique was used to look into food contamination by bacteria, household necessities, medical specimens, and Lyme borreliosis caused by tick infection, as well as to diagnose and treat the disease. The borrelia bacteria that cause infection are found in ticks and, later on, in human blood after they enter the host. The foregoing examples show how essential oils can stop bacterial infections in various samples but this method can also be applied in human medicine and tick-borne Lyme disease is taken here as representative for diagnosis and therapy of diseases caused by bacterial infections in humans. The effect of the antibiotics applied can be examined and the progress of an antibiotic therapy can be controlled until its final success is recognized.